Arabidopsis TFL2/LHP1 specifically associates with genes marked by trimethylation of histone H3 lysine 27. - Franziska Turck; François Roudier; Sara Farrona; Marie-Laure Martin-Magniette; Elodie Guillaume; Nicolas Buisine; Séverine Gagnot; Robert A Martienssen; George Coupland; Vincent Colot (PLoS Genetics)
TERMINAL FLOWER 2/LIKE HETEROCHROMATIN PROTEIN 1 (TFL2/LHP1) is the only Arabidopsis protein with overall sequence similarity to the HETEROCHROMATIN PROTEIN 1 (HP1) family of metazoans and S. pombe. TFL2/LHP1 represses transcription of numerous genes, including the flowering-time genes FLOWERING LOCUS T (FT) and FLOWERING LOCUS C (FLC), as well as the floral organ identity genes AGAMOUS (AG) and APETALA 3 (AP3). These genes are also regulated by proteins of the Polycomb repressive complex 2 (PRC2), and it has been proposed that TFL2/LHP1 represents a potential stabilizing factor of PRC2 activity. Here we show by chromatin immunoprecipitation and hybridization to an Arabidopsis Chromosome 4 tiling array (ChIP-chip) that TFL2/LHP1 associates with hundreds of small domains, almost all of which correspond to genes located within euchromatin. We investigated the chromatin marks to which TFL2/LHP1 binds and show that, in vitro, TFL2/LHP1 binds to histone H3 di- or tri-methylated at lysine 9 (H3K9me2 or H3K9me3), the marks recognized by HP1, and to histone H3 trimethylated at lysine 27 (H3K27me3), the mark deposited by PRC2. However, in vivo TFL2/LHP1 association with chromatin occurs almost exclusively and co-extensively with domains marked by H3K27me3, but not H3K9me2 or -3. Moreover, the distribution of H3K27me3 is unaffected in lhp1 mutant plants, indicating that unlike PRC2 components, TFL2/LHP1 is not involved in the deposition of this mark. Rather, our data suggest that TFL2/LHP1 recognizes specifically H3K27me3 in vivo as part of a mechanism that represses the expression of many genes targeted by PRC2.